Narrative Shift in Social Media News Reporting: A Case Study of Ferdy Sambo on Instagram - Amal, Muhammad Ihlasul; Mau, Muliadi; Sonni, Alem Febri (representamen, 2026)
The Ferdy Sambo case developed into a major institutional crisis in Indonesia, marked by inconsistent official statements, shifting chronologies, and growing public distrust toward the police. In the digital media environment, this crisis unfolded not only through the disclosure of new facts but also through ongoing transformations in narratives circulating within the online public sphere. This study examines how narrative shifts occurred in Instagram news coverage of the case by @narasinewsroom and analyzes the role of digital framing in shaping meaning during a legitimacy crisis. While previous framing studies tend to capture media representation at a single moment, this research highlights the temporal dynamics of narrative construction in social media-driven communication. It also emphasizes multimodal framing, integrating verbal, visual, and vocal elements, alongside the active role of audiences as prosumers in negotiating meaning. Using an interpretive qualitative approach, this study applies Gamson and Modigliani’s framing model combined with temporal narrative mapping. Nineteen posts were purposively selected from 182 Instagram uploads published between July 2022 and February 2023 to identify key narrative turning points. The findings reveal five phases of narrative shift: construction, disruption, exposure, escalation, and closure. The transition from the initial “shootout” narrative to the “murder plot” narrative indicates the erosion of institutional narrative authority. Multimodal framing devices and prosumer interactions play a crucial role in delegitimizing inconsistent official accounts and reinforcing alternative interpretations aligned with emerging evidence. This study demonstrates that narrative shift functions as an analytical indicator of institutional legitimacy crisis in digitally mediated communication and underscores the importance of coherent and transparent crisis communication in maintaining public trust in the digital era.